CFIUS reforms must be reformed - Theodore H. Moran (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2018)
Congress and the White House are proposing a fundamental "reform" of CFIUS regulations, via the Foreign Investment Risk Review Modernization Act. This Perspective argues that these so-called reforms would damage US interests and shows how the FIRRMA reforms must be reformed.
Keywords: 330